2008
DOI: 10.1039/b810853f
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry and kinetics of acetonylperoxy radical isomerisation and decomposition: a quantum chemistry and CVT/SCT approach

Abstract: CBS-QB3 calculations have been used to determine thermochemical and kinetic parameters of the isomerisation and decomposition reactions of the acetonylperoxy radical, CH3C(O)CH2OO* , which has been formed via the reaction of acetonyl radical with O2 leading to the formation of an energised peroxy adduct with a calculated well depth of near 111 kJ mol(-1). This species can undergo subsequent 1,5 and 1,3 H-shifts to give the primary and secondary radicals: C*H2C(O)CH2OOH and CH3C(O)C*HOOH, respectively, or rearr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 86 publications
4
15
0
Order By: Relevance
“…The initial reaction is a 1,5 H-shift from the methyl group with an MC-TST calculated rate coefficient of 5.9 × 10 -6 s -1 . The high barrier resulting in low rate coefficient for this reaction is in agreement with previous studies 17, [72][73][74][75] and has been ascribed to the strain in the TS induced by the sp 2 -hybridized carbon atom reducing the flexibility. 72 This means that the 1,5 H-shift is negligible from the thermalized peroxy radical under all relevant time scales and any possible OH-recycling from reactions following this Hshift thus relies on it occurring via excess energy from the O2-addition to the CH3C(O)CH2O2…”
Section: Reactionsupporting
confidence: 91%
“…The initial reaction is a 1,5 H-shift from the methyl group with an MC-TST calculated rate coefficient of 5.9 × 10 -6 s -1 . The high barrier resulting in low rate coefficient for this reaction is in agreement with previous studies 17, [72][73][74][75] and has been ascribed to the strain in the TS induced by the sp 2 -hybridized carbon atom reducing the flexibility. 72 This means that the 1,5 H-shift is negligible from the thermalized peroxy radical under all relevant time scales and any possible OH-recycling from reactions following this Hshift thus relies on it occurring via excess energy from the O2-addition to the CH3C(O)CH2O2…”
Section: Reactionsupporting
confidence: 91%
“…The bulk solvent effect is described by the polarizable continuum method (PCM) [44,45] at 298.15 K and 1.0 atm by performing SCRF calculations at the B3LYP/6-311++G(d,p) level. It has been shown that the thermodynamics results obtained with the CBS-QB3 [46] and B2PLYP [47] levels are comparable with the experimental data [48][49][50]. Therefore, the relative stability of considered tautomers and the equilibrium constants between these tautomers in the gas phase as well as in the solutions are calculated at the CBS-QB3 and B2PLYP/6-31+G(2d,p) levels.…”
Section: Methods Of Calculationssupporting
confidence: 56%
“…For the 1-methylvinoxy (or acetonyl) radical, there is again a remarkable agreement between the experimental estimate 88 of the O 2 addition barrier, −0.60 ± 0.05 kcal mol −1 , and the CBS-QB3 barrier of −0.6 kcal mol −1 reported by El-Nahas and coworkers 38 and newly computed by the author of this review using Gaussian 09 52 . (Again, the barrier previously reported by Kuwata and coworkers 26 of 2.4 kcal mol −1 was based on a faulty implementation of CBS-QB3 in Gaussian 98 71 .)…”
Section: Primary Ozonidesupporting
confidence: 82%
“…El-Nahas and coworkers 38 note that the negative CBS-QB3 barrier implies the existence of a prereactive complex between the 1-methylvinoxy and the O 2 , but searches of the potential energy surface with the B3LYP/6-311G(d,p) model chemistry revealed no such minimum. An estimate of the reaction barrier based on a potential energy scan using the BB1K/cc-pVTZ model chemistry gives a value of 3.5 kcal mol −1 50 , and 298 K activation enthalpies using B3LYP are between 2.0 and 2.4 kcal mol −1 38, 49 .…”
Section: Primary Ozonidementioning
confidence: 99%